PENGARUH PEMBERIAN PROBIOTIK GDM PADA MEDIA PEMELIHARAAN TERHADAP KUALITAS AIR DAN PERTUMBUHAN BENIH IKAN BAWAL (Colossoma macropomum) - Anzarwati, Tika; Putriningtias, Andika; Isma, Muhammad Fauzan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the effect of giving GDM probiotics on maintenance media on water quality and growth of pomfret fish. The method used was a completely randomized design (RAL) with 4 treatments and 3 replications, namely P0 (without the addition of probiotics). P1 (addition of probiotics 1.5 ml/L). P2 (addition of probiotic 2.0 ml/L) and P3 (addition of probiotic 2.5 ml/L). Each treatment used seeds measuring 4-5 cm. Parameters observed during the study were water quality, absolute weight growth (PBM), absolute length growth (PPM), survival rate (SR), and specific growth rate (SGR). Based on the analysis of variance, it was found that the treatment given had a significant effect (P<0.05) on absolute weight growth, absolute length growth, SR survival rate, and specific growth rate. Also, based on Duncan's test, treatment P1 (1.5 ml/L) was the best treatment.